Students' Academic Anxiety in Preparing for Final Examination in View of Gender - Adrianus Zega (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine differences in student academic anxiety ahead of the Preparing for Final Project regarding gender. The research subjects amounted to 50 people who were taken using the cluster sampling technique so that all faculties could be represented. The measuring instrument used is a measuring instrument for academic anxiety. Based on the calculation of differences in academic anxiety between male and female students, obtained the sig value of 0.087 ≥ 0.05. It shows no significant difference between academic anxiety in male and female students. The average academic anxiety in male students is 61.65, with a standard deviation of 1.215, while the average female is 60.89, with a standard deviation of 1.137. Both male and female students experience academic anxiety before the Final Examination, so there is no significant difference in academic anxiety.